Essential Readings in Light Metals, Volume 1, Alumina and Bauxite - Donaldson, Don; Raahauge, Benny (The Minerals, Metals & Materials Series,, 2016)
ONE OF A FOUR-BOOK COLLECTION SPOTLIGHTING CLASSIC ARTICLES Five decades of landmark original research findings and reviews Highlighting some of the most important findings reported over the past five decades, this volume features some of the best technical papers published on alumina and bauxite from 1963 to 2011. Papers have been divided into thirteen subject sections for ease of access. Each section has a brief introduction and a list of recommended articles for researchers interested in exploring each subject in greater depth. Only about fifteen percent of the alumina and bauxite papers ever published in Light Metals were chosen for this volume. Selection was based on a rigorous review process. Among the papers, readers will find landmark original research findings and expert reviews summarizing current thinking on key topics at the time of publication. From basic research to advanced applications, the articles published in this volume collectively represent our body of knowledge in alumina and bauxite. Students, scientists, and engineers should turn to this volume to discover the historical development of alumina and bauxite research as well as the current state of the science and the technology. Moreover, the papers published in this volume will serve as a springboard for future research and discoveries.